Neuroendocrine differentiation in the setting of prostatic carcinoma: contemporary assessment of a consecutive series. Issue 2 (11th July 2022) - Gopalan, Anuradha; Al‐Ahmadie, Hikmat; Chen, Ying‐Bei; Sarungbam, Judy; Sirintrapun, S. Joseph; Tickoo, Satish K; Reuter, Victor E; Fine, Samson W
Abstract : Aim: Clinicopathologic characterisation of a contemporary series of neuroendocrine (NE) differentiation in the setting of prostatic carcinoma (PCa) was examined. Methods and results: We reviewed institutional databases for in‐house cases with a history of PCa and histopathologic evidence of NE differentiation during the disease course. In all, 79 cases were identified: 32 primary and 47 metastases. Metastatic lesions were in liver ( n = 15), lymph node ( n = 9), bone ( n = 6), lung ( n = 3), brain ( n = 1), and other sites ( n = 13). In all, 63 of 76 (82%) cases with NE differentiation and available history were posttherapy: six postradiation therapy (RT), 24 post‐ androgen–deprivation therapy (ADT), and 33 post‐RT + ADT. Morphologic assessment ( n = 79): (i) 23 pure small‐cell/high‐grade NE carcinoma (HGNEC): 20/23 metastatic; (ii) 10 combined high‐grade PCa and small‐cell/HGNEC: 9/10 primary; (iii) 15 PCa with diffuse NE immunohistochemistry (IHC) marker positivity/differentiation, associated with nested to sheet‐like growth of cells with abundant cytoplasm and prominent nucleoli, yet diffuse positivity for at least one prostatic and one NE IHC marker: all metastatic; (iv) 11 PCa with patchy NE differentiation, displaying more than single‐cell positivity for NE IHC: five primary / six metastatic; (v) nine PCa with focal NE marker positive cells: four primary / five metastatic; (vi) 11 PCa with 'Paneth cell‐like' change: all primary. Conclusions: In this contemporary series, the majority of NE differentiation in the setting of PCa was seen posttherapy. We highlight the tendencies of small‐cell/HGNEC and PCa with diffuse NE differentiation by IHC to occur in metastatic settings, while morphologically combined high‐grade PCa + small‐cell/HGNEC and 'Paneth cell‐like' change occur in primary disease. Abstract : Incidence, setting (primary v. metastatic), and therapeutic history of various neuroendocrine manifestations in the setting of prostatic carcinoma.